THE IMPACT OF FINTECH ON FINANCIAL LITERACY AND INCLUSION AT CILACAP’S PHARMACY WITH THE MILES AND HUBERMAN MODEL - Lia Ernawati; Elisa Issusilaningtyas; Herlin Natasya Sefiani (Jurnal Ekonomi, 2022)
Development of fintech Keep going continues, not only limited distribution funds which Becomes a strength of main sector fintech. However, fintech innovation Becomes system payment which boom. With the more advanced technology, pharmacy industries must follow developments to be able to compete, because the competitive advantage is rooted in superior financial performance and market positioning identification of the problem in this research is the development of technology in the field of Financial information that results in the behavior of consumers in To do transactions which more choose by digitally. Is fintech able to positively influence financial literacy and inclusion at pharmacies in Cilacap. This research method uses qualitative data with the Miles and Huberman models. The results of qualitative research on 20 resource persons gave the results that Fintech influences and has a positive impact on financial literacy and the inclusion of pharmacies in Cilacap.